Need Help?

  • Notes
  • Comments & Questions

Evaluate \(\int \sqrt{1+e^{2 x}} d x\)

let \(t=\sqrt{1+e^{2 x}} \longrightarrow t^{2}=1+e^{2 x} \longrightarrow 2 t d t=2 e^{2 x} d x \rightarrow d x=\frac{2td t}{2 e^{2 x}}\)

\(d x=t \cdot e^{-2 x} d t\)

\(\int \sqrt{1+e^{2 x}} d x=\int t \cdot t \cdot e^{-2 x} d t=\int \frac{t^{2} d t}{e^{2 x}}\)

\(t^{2}=1+e^{2 x}, e^{2 x}=t^{2}-1\)

\(\int \sqrt{1+e^{2 x}} d x=\int \frac{t^{2} d t}{t^{2}-1}\)

long division

\(=\int\left(1+\frac{1}{t^{2}-1}\right) d t\)

\(=\int 1 d t+\int \frac{1}{t^{2}-1} d t=t+\int \frac{1}{(t-1)(t+1)}dt\)

\(\int \frac{1}{(t-1)(t+1)}=\int \frac{A}{t-1} d t+\int \frac{B}{t+1} d t\)

\(A=(t-1) \cdot\left.\frac{1}{(t-1)(t+1)}\right|_{t=1}=\frac{1}{t+1} |_{t=1}=\frac{1}{2}\)

\(B=(t+1) \cdot\left.\frac{1}{(t-1)(t+1)}\right|_{t=-1}=\frac{1}{t-1} |_{t=-1}=-\frac{1}{2}\)

\(\int \frac{1 d t}{(t-1)(t+1)}=\int \frac{\frac{1}{2}}{t-1} d t+\int \frac{-\frac{1}{2}}{t+1} d t\)

\(=\frac{1}{2} \int \frac{1}{t-1} d t-\frac{1}{2} \int \frac{1}{t+1} d t\)

\(\int \frac {1}{(t-1)(t+1)}dt=\frac{1}{2} \ln |t-1|-\frac{1}{2}|n| t+1 |+c\)

\(\int \sqrt{1+e^{2 x}} d x=\int 1 d t+\int \frac{1 d t}{(t-1)(t+1)}\)

\(\int \sqrt{1+e^{2 x}} d x=t+\frac{1}{2} \ln |t-1|-\frac{1}{2} \ln |t+1|+c\)

\(\begin{array}{l}{a \ln |{b}|=\ln |b^a|} \\ {\ln |a|-\ln |b|=\ln \left|\frac{a}{b}\right|}\end{array}\)

\(\int \sqrt{1+e^{2 x}} d x=t+\ln \left|(t-1)^{\frac{1}{2}}\right|-\ln \left|(t+1)^{\frac{1}{2}}\right|+c\)

\(\int \sqrt{1+e^{2 x}} d x=t+\ln |\sqrt{(t-1)}|-\ln |\sqrt{(t+1)}|+c\)

\(\int \sqrt{1+e^{2 x}} d x=t+\ln \left|\frac{\sqrt{t-1}}{\sqrt{t+1}}\right|+c\)

\(t=\sqrt{1+e^{2 x}}\)

\(\int \sqrt{1+e^{2 x}}=\sqrt{1+e^{2 x}}+\ln \left|\sqrt{\frac{\sqrt{1+e^{2x}}-1}{\sqrt{1+ e^{2x}}+1}}\right|+c\)

Evaluate \(\int \frac{d x}{x^{1 / 2}+x^{1 / 3}}\)

\(2,3 \rightarrow 6\)

let \(u=x^{\frac{1}{6}} \Rightarrow x=u^{6} \Rightarrow d x=6 u^{5} d u\)

\(x^{\frac{1}{2}}=u^{3} \qquad x^{\frac{1}{3}}=u^{2}\)

\(\int \frac{{6} u^{5} d u}{u^{3}+u^{2}}=6 \int \frac{u^{5}}{u^{3}+u^{2}} d u\)

\(=6 \int \frac{u^{2}\cdot u^{3}}{u^{2}(u+1)}  d u=6 \int \frac{u^{3}}{u+1} d u\)

\(\int \frac{d x}{x^{1 / 2}+x^{1 / 3}}=6 \int \frac{u^{3}}{u+1} d u=6 \int u^{2}-u+1-\frac{1}{u+1}\)

\(\int \frac{d x}{x^{1/2}+x^{1/3}}=6\left[\frac{u^{3}}{3}-\frac{u^{2}}{2}+u-\ln |u+1|\right]+c\)

\(\int \frac{d x}{x^{1 / 2}+x^{{1}/{3}}}=2 u^{3}-3 u^{2}+6 u-\ln |u+1|+c\)

\(\int \frac{d x}{x^{1/2}+x^{1/3}}=2 x^{\frac{1}{6} \cdot 3}-3 x^{\frac{1}{6}\cdot 2}+6 x^{\frac{1}{6}}-\ln \left|x^\frac{1}{6}+1\right|+c\)

\(\int \frac{d x}{x^{1/2}+x^{1/3}}=2 \sqrt{x}-3 x^\frac {1}{3}+6 x^\frac {1}{6}-\ln \left|x^\frac {1}{6}+1\right|+C\)

No comments yet

Join the conversation

Join Notatee Today!